Alternatif Kebijakan Ketidaklengkapan Pengisian Rekam Medis Pasien Tindakan Catheterisasi di Rumah Sakit : Alternative Policies for Incomplete Completion of Patient Medical Records for Catheterization in Hospitals - Mukarom, Muhammad Zulfikri; Septiawan, Catur (Journal of Public Health Education, 2022)
Introduction: Medical records are files that contain notes and documents regarding patient identity and other services provided to patients at health service facilities. According to Minister of Health Regulation No. 269/Menkes/Per/III/2008 concerning Medical Records, it explains that medical records are files containing notes and documents regarding patient identity, examinations, treatment, procedures, and other services that have been provided to patients. Objective: To analyze and recommend alternative policies for incomplete filling in medical records of patients undergoing catheterization procedures in 2019. Methods: This research is descriptive using qualitative methods. The data collection instrument used was an in-depth interview guide assisted by a voice recorder and writing equipment. The sampling technique used in this research was purposive sampling. Meanwhile, instruments for direct observation use a digital camera (cellphone) to make it more effective and efficient, as well as a checklist for supporting documents and recordings. Results: The roots of the problems that affect the completeness of medical records are the time to complete medical records is insufficient/busy, the motivation of medical staff in filling out medical record documents is still lacking, there are no sanctions for health workers who do not complete medical records, monitoring and evaluating incomplete record documents medical assistance by bringing in medical personnel is still not implemented in the hospital, there is a lack of socialization of the SOP for filling out medical records, the arrangement of medical record forms is less systematic, so it needs to be simplified and integrated, the implementation of filling in is still not following the SOP and needs to be reviewed, limited financial resources to support the evaluation of completeness medical record file. Conclusion: Completeness in filling out medical records is close to 100%, which occurs in terms of clarity of condition or diagnosis, consistent input, and reasons for service, with the majority of results showing a high average percentage, but there are still incomplete recordings in several elements that occur in Informed Consent, review of records and information on the person responsible for the costs. Management is still trying to fulfill this policy by planning, evaluating, and modifying the old medical record to an electronic Medical Record program. Clarity and efficiency of electronic medical records can be an appropriate policy alternative because they are useful for minimizing indiscipline in filling out medical records for catheterization patients.